Exploring the Limits of Transgression and Violence within the Israeli-Palestinian Conflict - Katz, Yaron (Randwick International of Social Science Journal, 2024)
ABSTRACT Transgression and violence, when intertwined, challenge societal norms and provoke moral dilemmas within democratic frameworks. This is particularly evident in the context of the Israeli-Palestinian conflict, a significant case study for this research. Transgression, breaking or exceeding societal norms, can manifest through civil disobedience or defiant behavior to challenge oppressive systems. Violence, conversely, refers to the deliberate use of physical force or authority to cause harm or destruction. The escalation from transgression to violence occurs when individuals or groups resort to aggression to restore order or assert power. This shift is particularly evident in protests or riots triggered by social injustices or political oppression. Such events can intensify due to radical democratic possibilities and the influence of technology. Digital platforms, with their crucial role in shaping public opinion, mobilizing individuals, and strengthening collective fears about social change, significantly contribute to the escalation of conflict. They also facilitate the production of panic and misinformation, complicating the landscape of public discourse and protest. In the Israeli-Palestinian conflict, deep-rooted historical and political complexities mark the intersection of transgression and violence. Territorial disputes and competing national narratives drive both Israeli and Palestinian actions. Resistance to the Israeli occupation often involves transgressive acts such as protests or violent resistance, while Israeli security measures, perceived as transgressions by Palestinians, exacerbate tensions and contribute to ongoing violence.